GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 4017 species occurrences available in GBIF matching the query: TaxonKey: Petromyzon marinus Linnaeus, 1758 HasCoordinate: true HasGeospatialIssue: false. The dataset includes 4017 records from 69 constituent datasets: 3 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD unverified freshwater fish data up to current day. 89 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Vertebrate Observation Records, other than Birds. Pre-2010 for Cumbria. 22 records from Geographically tagged INSDC sequences. 2 records from Countryside Council for Wales - Pembrokeshire Marine Species Atlas. 3 records from CUMV Fish Collection (Arctos). 99 records from Inventario Español de Especies Terrestres (MAGRAMA). 3 records from National System of Protected Areas in Poland - Animals. 8 records from KUBI Ichthyology Collection. 67 records from DFO Maritimes Research Vessel Trawl Surveys Fish Observations (OBIS Canada). 3 records from Museu de Ciències Naturals de Barcelona: MCNB-Cord. 1 records from Fish Specimens. 37 records from Fish collection, Natural History Museum, University of Oslo. 83 records from Ohio State University Fish Division (OSUM). 1 records from North & East Yorkshire Ecological Data Centre - North and East Yorkshire Ecological Data Centre - Non-sensitive Records from all taxonomic groups.. 1 records from CNPE/Coleccion Nacional de Peces. 13 records from UF FLMNH Ichthyology. 11 records from NINA Vanndata fisk. 45 records from Royal Netherlands Institute for Sea Research (NIOZ) - Kom Fyke Mokbaai. 65 records from NCSM Fishes Collection. 80 records from Environment Agency - Environment Agency Rare and Protected Species records v1. 406 records from Biological Records Centre - Database for the Atlas of Freshwater Fishes. 18 records from Countryside Council for Wales - Lamprey Survey Data. 4 records from Biological and palaeontological collection and observation data MNHNL. 212 records from Atlas of Danish Fishes. 15 records from Atlantic Reference Centre (OBIS Canada). 65 records from North Carolina State Museum of Natural Sciences Fishes Collection. 216 records from Inventaire National du Patrimoine Naturel : Atlas des poissons d'eau douce de France métropolitaine (2011). 9 records from SLU Aqua Institute of Freshwater Research Swedish Electrofishing Registry - SERS. 5 records from Taxonomic Information Sytem for the Belgian coastal area (EurOBIS). 426 records from Canadian Museum of Nature Fish Collection. 6 records from SAIAB: National Fish Collection (1880-2008). 2 records from RAVON (NL) - Fish observations extracted from Hoek (1888) and Hoek (1897). 1 records from Sheffield Biological Records Centre - Sheffield Biological Records Centre- Non-sensitive Records from all taxonomic groups.. 1 records from VIS - Fishes in estuarine waters in Flanders, Belgium. 12 records from Fishbase. 1 records from Freshwater fishes of the Western Balkans. 2 records from Colección Nacional de Peces del IBUNAM. 1 records from Gronau - auf der Suche nach dem Neunauge. 1 records from Bay of Fundy Species List (OBIS Canada). 1 records from Countryside Council for Wales - Shad Monitoring data. 5 records from Collection Pisces SMF. 203 records from Inventaire National du Patrimoine Naturel : Poissons d'eau douce de France. 32 records from NRM-Fishes. 2 records from South East Wales Biodiversity Records Centre - CCW Regional Data : South East Wales Non-sensitive Species Records. 4 records from Monitoring data from the federal state North Rhine-Westphalia (Germany). 295 records from Artdata. 26 records from Countryside Council for Wales - CCW Freshwater Fish ad hoc Records for Article 17 Reporting. 8 records from Fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 280 records from United States Geological Survey Nonindigenous Aquatic Species Database. 3 records from Tulane University Museum of Natural History. 4 records from Freshwater fishes of Italy. 31 records from NMNH occurrence DwC-A. 95 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Peces Continentales. 2 records from Oregon State Ichthyology Collection. 2 records from Natural History Museum (London) Collection Specimens. 8 records from Ichthyology. 4 records from CAS Ichthyology (ICH). 1 records from Centre for Environmental Data and Recording - Marine Data from Northern Ireland. 301 records from Ichthyology Collection - Royal Ontario Museum. 24 records from Rare marine fishes taken in Irish waters from 1786 to 2008. 120 records from Fish specimens. 135 records from Scottish Natural Heritage - Site Condition Monitoring Records from surveys of lamprey species in five river SACs in Scotland. 11 records from Vertebrate Zoology Division - Ichthyology, Yale Peabody Museum. 1 records from Bristol Regional Environmental Records Centre - BRERC October 2009. 1 records from Electronic Atlas of Ichthyoplankton on the Scotian Shelf of North America (OBIS Canada). 211 records from Inventaire National du Patrimoine Naturel : Données ONEMA sur les poissons et écrevisses d'eau douce.. 165 records from Museum of Comparative Zoology, Harvard University. 2 records from KUBI Ichthyology Tissue Collection. 1 records from Priest Pot species list, Cumbria, Britain.
Keywords: GBIF; biodiversity; species occurrences